Analysis of Cash Flow Patterns of Companies that Indicate Financial Distress - Poespawijaya, Natalia (Research Parks Publishers, 2024)
This study aims to analyze cash flow patterns in companies experiencing financial distress. Financial distress is a condition in which a company faces serious financial difficulties, and this condition can affect the overall financial health of the company. This study uses a quantitative analysis method to identify cash flow patterns in companies that are experiencing financial distress by collecting financial data from several healthy companies and identified as experiencing financial distress in the 2020-2022 period based on secondary data from the IDX financial statements. The results of this study are expected to provide a deeper understanding of cash flow patterns in companies experiencing financial distress and several other factors that influence it. The implications of this analysis are expected to assist in designing appropriate financial improvement strategies to overcome financial distress situations as well as provide insight to stakeholders regarding actions that can be taken to improve the company's financial health in the future.